Impact of prostaglandin glaucoma drops on platelet-activating factor action: an in vitro study - Moschos MM; Nitoda E; Chatziralli IP; Panos GD; Demopoulos CA (Dove Medical Press, 2016)
Marilita M Moschos,1 Eirini Nitoda,1 Irini P Chatziralli,1 Georgios D Panos,2 Constantinos A Demopoulos3 11st Department of Ophthalmology, Medical School, National and Kapodistrian University of Athens, Athens, Greece; 2Department of Ophthalmology, Geneva University Hospitals (HUG), University of Geneva, Geneva, Switzerland; 3Laboratory of Biochemistry, National and Kapodistrian University of Athens, Athens, Greece Aim: The aim of this study was to investigate the effect of different prostaglandin analogs on platelet-activating factor (PAF) levels.Methods: Three prostaglandin analogs were selected: bimatoprost 0.3 mg/mL, latanoprost 50 µg/mL, and tafluprost 15 µg/mL. Each drug sample was tested for its ability to cause platelet aggregation, which was measured as PAF-induced aggregation, before and after the addition of various concentrations of the examined sample, creating a linear curve of percentage inhibition (ranging from 0% to 100%) versus different concentrations of the sample. The concentration of the sample that inhibited 50% PAF-induced aggregation was calculated based on this curve, and this value was defined as IC50. In addition, the effect of eye drops on PAF metabolism was examined, through an in vitro analysis on PAF basic metabolic enzymes (PAF-cholinephosphotransferase, PAF-acetyl-CoA:1-O-alkyl-sn-glycero-3-phosphocholine acetyltransferase, and PAF-acetylhydrolase).Results: The IC50 values for Lumigan UD® (bimatoprost 0.3 mg/mL), Monoprost® (latanoprost 50 µg/mL), and Saflutan (tafluprost 15 µg/mL) were 8.7, 0.28, and 1.4 µg/mL, respectively.Discussion: All three prostaglandin analogs suspended PAF, but bimatoprost induced the most potent inhibition, compared to tafluprost and to the weak effect of latanoprost. Keywords: glaucoma, platelet-activating factor, prostaglandin analogs, treatment, platelet aggregation